2021
DOI: 10.1115/1.4053033
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Lubricating Performance of h-BN/GF Nanoparticles as Oil Additives for Steel-Steel Contact

Abstract: The major objective of this work is to investigate the synergistic lubricating performance of hexagonal boron nitride (h-BN) and graphite fluoride (GF) nanoparticles (NPs) as lubricant additive in white oil. The tribological tests were carried out on steel-steel contacts using reciprocating ball-on-disk tribometer. Compared with white oil, addition of 0.1 wt. % h-BN/GF reduced the friction coefficient, wear rate and wear depth by 41.1 %, 89.1 %, and 92.3 %, respectively. Furthermore, when the mass ratio of h-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Various solid additives, 2 such as graphene 3–6 and molybdenum disulfide (MoS 2 ), 7–9 were added to grease to further improve its tribological performance. The hexagonal boron nitride (h‐BN) has a layered crystal structure, creating low interfacial shear strength so that it becomes a compelling alternative to other inorganic solid lubricants 10–12 . Therefore, the h‐BN particle has also been widely added into grease for improving lubrication and anti‐wear performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various solid additives, 2 such as graphene 3–6 and molybdenum disulfide (MoS 2 ), 7–9 were added to grease to further improve its tribological performance. The hexagonal boron nitride (h‐BN) has a layered crystal structure, creating low interfacial shear strength so that it becomes a compelling alternative to other inorganic solid lubricants 10–12 . Therefore, the h‐BN particle has also been widely added into grease for improving lubrication and anti‐wear performance.…”
Section: Introductionmentioning
confidence: 99%
“…The hexagonal boron nitride (h-BN) has a layered crystal structure, creating low interfacial shear strength so that it becomes a compelling alternative to other inorganic solid lubricants. [10][11][12] Therefore, the h-BN particle has also been widely added into grease for improving lubrication and anti-wear performance. For example, the h-BN micro-particles with a diameter of 4-10 μm served as a lubricating grease-2 additive, and the experimental results showed that appending h-BN to the grease-2 resulted in an excellent property in the shaft-sleeve slide regime.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low graphitic loadings (sub-10 wt%) into copper films greatly diminish frictional losses under low contact pressure nano-and macrotribological testing. 44,45,21 Fluorographenes have been utilized in oil-based [46][47][48][49] and polymer-based [50][51][52] lubricating formulations. However, the incorporation of fluorographenes into metal composites have scarcely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…66 Furthermore, low graphitic loadings (sub-10 wt%) into copper films greatly diminish frictional losses under low contact pressure nano-and macrotribological testing. 38,67,68 Flurographenes have been utilized in oil-based [69][70][71][72][73] and polymer-based [74][75][76] lubricating formulations. However, the incorporation of fluorographenes into metal composites has scarcely been explored.…”
Section: Introductionmentioning
confidence: 99%